A new germline VHL gene mutation in three patients with apparently sporadic pheochromocytoma. (25th January 2013) - D'Elia, Angela V.; Grimaldi, Franco; Pizzolitto, Stefano; De Maglio, Giovanna; Bregant, Elisa; Passon, Nadia; Franzoni, Alessandra; Verrienti, Antonella; Tamburrano, Giulia; Durante, Cosimo; Filetti, Sebastiano; Fogolari, Federico; et al.
Summary: Context: Germline mutations in four genes (RET, VHL, SDHB and SDHD) are detected in about 17% of patients with apparently sporadic pheochromocytoma. Thus, genetic screening of all patients with this disease is suggested for a rational diagnostic approach and management. Objective: To report the clinical, biochemical and genetic analysis of three unrelated patients affected by pheochromocytoma. Design and patients: All the coding regions and exon–intron boundaries of RET, VHL, SDHB and SDHD genes were sequenced in three unrelated patients with intra‐adrenal pheochromocytoma: a 17‐year‐old girl, a 15‐year‐old boy and a 73‐year‐old man. The family history of all three cases was negative for von Hippel–Lindau lesions or other types of endocrine tumours. Structural modelling of the VHL protein was then performed. Results: We identified a novel germline VHL gene point mutation, a G to A nucleotide substitution in exon 3, leading to an aspartate to asparagine amino acid change in codon 197 (D197N). No mutations were found in RET, SDHB and SDHD genes. Structural modelling of the VHL protein suggests that the D197N mutation could have a functional role. Conclusions: Our study expands the number of VHL gene known mutations and indicates the usefulness of performing the genetic analysis in all patients with apparently sporadic pheochromocytoma.